Analysis of Design Changes from Main Engine Diesel Engine to Electric Engine on Fishing Vessels - Ramadhani, Dimitry Rizal; Pranatal, Erifive (Institut Teknologi Adhi Tama Surabaya, 2024)
Fishing vessels in Indonesia conventionally use diesel engines as their main propulsion engine. However, the use of diesel engines has quite a bad impact on the surrounding environment. So the latest innovations using alternative energy are needed. One of them is the use of electric engines as a replacement for diesel engines in the ship's main propulsion engine. The use of this electric machine will have a friendly impact on the environment. Apart from that, you don't need to spend a lot of money to maintain this electric machine. We can see this by comparing the ship's thrust requirements with maximum speed.